Effect of orthodontic brackets and different wires on radiofrequency heating and magnetic field interactions during 3-T MRI - Görgülü, S (The British Institute of Radiology., 2014)
OBJECTIVES: To evaluate the heating and magnetic field interactions of fixed orthodontic appliances with different wires and ligaments in a 3-T MRI environment and to estimate the safety of these orthodontic materials. METHODS: 40 non-carious extracted human maxillary teeth were embedded in polyvinyl chloride boxes, and orthodontic brackets were bonded. Nickel–titanium and stainless steel arch wires, and elastic and stainless steel ligaments were used to obtain four experimental groups in total. Specimens were evaluated at 3 T for radiofrequency heating and magnetic field interactions. Radiofrequency heating was evaluated by placing specimens in a cylindrical plastic container filled with isotonic solution and measuring changes in temperature after T(1) weighted axial sequencing and after completion of all sequences. Translational attraction and torque values of specimens were also evaluated. One-way ANOVA test was used to compare continuous variables of temperature change. Significance was set at p < 0.05. RESULTS: None of the groups exhibited excessive heating (highest temperature change: <3.04 °C), with the maximum increase in temperature observed at the end of the T(1) weighted axial sequence. Magnetic field interactions changed depending on the material used. Although the brackets presented minor interactions that would not cause movement in situ, nickel–titanium and stainless steel wires presented great interactions that may pose a risk for the patient. CONCLUSIONS: The temperature changes of the specimens were considered to be within acceptable ranges. With regard to magnetic field interactions, brackets can be considered “MR safe”; however, it would be safe to replace the wires before MRI.